2022
DOI: 10.3389/fonc.2022.843175
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Relative Biological Effectiveness (RBE) for Mandible Osteoradionecrosis (ORN) in Head and Neck Cancer Patients Treated With Pencil-Beam-Scanning Proton Therapy (PBSPT): A Retrospective, Case-Matched Cohort Study

Abstract: PurposeTo retrospectively investigate empirical relative biological effectiveness (RBE) for mandible osteoradionecrosis (ORN) in head and neck (H&N) cancer patients treated with pencil-beam-scanning proton therapy (PBSPT).MethodsWe included 1,266 H&N cancer patients, of which, 931 patients were treated with volumetric-modulated arc therapy (VMAT) and 335 were treated with PBSPT. Among them, 26 VMAT and 9 PBSPT patients experienced mandible ORN (ORN group), while all others were included in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 41 publications
0
23
0
Order By: Relevance
“…This dose engine has been fully commissioned and benchmarked with other MC codes 68,71–75 . It has been incorporated in our in‐house treatment planning system, Shiva, 39,55,76–79 and clinically used as our second monitor unit check system 68,71 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This dose engine has been fully commissioned and benchmarked with other MC codes 68,71–75 . It has been incorporated in our in‐house treatment planning system, Shiva, 39,55,76–79 and clinically used as our second monitor unit check system 68,71 …”
Section: Methodsmentioning
confidence: 99%
“…[67][68][69][70] This dose engine has been fully commissioned and benchmarked with other MC codes. 68,[71][72][73][74][75] It has been incorporated in our in-house treatment planning system, Shiva, 39,55,[76][77][78][79] and clinically used as our second monitor unit check system. 68,71 The dose-averaged LET 45,69 was used to calculate the LET at each voxel from multiple fields.…”
Section: Voxel-based Dose-let Volume Histogram (Dlvh)mentioning
confidence: 99%
See 1 more Smart Citation
“…The adverse events after PBT are more complex than photon therapy due to the unique non-linear characteristic of the relationship of RBE with dose and LET d in PBT. 6,8,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] A newly developed tool, dose-LET d volume histogram (DLVH), was developed and was able to correlate high LET d and high dose with rectal adverse events. 26,28 It was reported that high LET d (≥2.5 keV/µm) volume in the rectum might result in a higher incidence rate of grade≥2 (CACTE V4.0) rectal bleeding in prostate cancer patients treated with proton therapy, even though the corresponding dose volume was moderate.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Yang et al recently estimated empirical RBEs for mandible osteoradionecrosis in HNC patients treated with pencil beam scanning protons versus photon-based volumetric modulated arc therapy, using a case-matched cohort design. Depending on dose cut-off, the estimated RBEs were 1.24–1.58 at moderate dose levels [29] . Evidently, there is a need for conventions and development of appropriate methods for clinical studies of proton RBE, and to harmonize LET collection across centers [30] .…”
mentioning
confidence: 99%